Review of mid-infrared mode-locked laser sources in the 2.0 μ m–3.5 μ m spectral region - Ma, Jie (2019)
Ultrafast laser sources operating in the mid-infrared (mid-IR) region, which contains the characteristic fingerprint spectra of many important molecules and transparent windows of atmosphere, are of significant importance in a variety of applications. Over the past decade, a significant progress has been made in the development of inexpensive, compact, high-efficiency mid-IR ultrafast mode-locked lasers in the picosecond and femtosecond domains that cover the 2.0 μm–3.5 μm spectral region. These achievements open new opportunities for applications in areas such as molecular spectroscopy, frequency metrology, material processing, and medical diagnostics and treatment. In this review, starting with the introduction of mid-IR mode-locking techniques, we mainly summarize and review the recent progress of mid-IR mode-locked laser sources, including Tm3+-, Ho3+-, and Tm3+/Ho3+-doped all-solid-state and fiber lasers for the 2.0 μm spectral region, Cr2+:ZnSe and Cr2+:ZnS lasers for the 2.4 μm region, and Er3+-, Ho3+/Pr3+-, and Dy3+-doped fluoride fiber lasers for the 2.8 μm–3.5 μm region. Then, some emerging and representative applications of mid-IR ultrafast mode-locked laser sources are presented and illustrated. Finally, outlooks and challenges for future development of ultrafast mid-IR laser sources are discussed and analyzed. The development of ultrafast mid-IR laser sources, together with the ongoing progress in related application technologies, will create new avenues of research and expand unexplored applications in scientific research, industry, and other fields.